Diagnostic Tools Using a Multi-Constellation Single-Receiver Single-Satellite Data Validation Method - El-Mowafy, Ahmed (Cambridge University Press, 2015)
The use of single-receiver single-satellite data validation parameters for numerical and graphical diagnostics of the multi-frequency observations is presented. This method validates Global Navigation Satellite System (GNSS) measurements of a single receiver where data from each satellite are independently processed using a geometry-free observation model with a reparameterised form of the unknowns. The method is applicable to any GNSS with any number of frequencies. The diagnostic tools are based on checking agreement of characteristics of the validation test statistics against theory. The use of these diagnostics in static and kinematic modes is demonstrated using multiple-frequency data from the three GNSS constellations; Global Positioning System (GPS), Globalnaya Navigatsionnaya Sputnikovaya Sistema (GLONASS) and Galileo.